2000
DOI: 10.1046/j.1365-2265.2000.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and penile erection: evidence for a direct relationship between free testosterone and cavernous vasodilation in men with erectile dysfunction

Abstract: These results indicate that in men with erectile dysfunction low free testosterone may correlate independently of age with the impaired relaxation of cavernous endothelial and corporeal smooth muscle cells to a vasoactive challenge. These findings give clinical support to the experimental knowledge of the importance of androgens in regulating smooth muscle function in the penis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
2
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 40 publications
4
136
2
4
Order By: Relevance
“…65,[88][89][90] In men with erectile dysfunction, low free testosterone levels correlate with impaired relaxation of cavernous endothelial and corporeal smooth muscle cells to a vasoactive challenge. 91 A direct effect of testosterone is feasible as testosterone modulates expression of endothelial nitric oxide synthase and phosphodiesterase type 5 (PDE5) within penile tissues. [92][93][94] Testosterone therapy can improve IIEF scores in men who do not respond to PDE5 inhibitors by improving sexual desire and orgasmic function and increasing penile arterial inflow during sexual stimulation.…”
Section: Testosterone and Sexual Health In Aging Menmentioning
confidence: 99%
“…65,[88][89][90] In men with erectile dysfunction, low free testosterone levels correlate with impaired relaxation of cavernous endothelial and corporeal smooth muscle cells to a vasoactive challenge. 91 A direct effect of testosterone is feasible as testosterone modulates expression of endothelial nitric oxide synthase and phosphodiesterase type 5 (PDE5) within penile tissues. [92][93][94] Testosterone therapy can improve IIEF scores in men who do not respond to PDE5 inhibitors by improving sexual desire and orgasmic function and increasing penile arterial inflow during sexual stimulation.…”
Section: Testosterone and Sexual Health In Aging Menmentioning
confidence: 99%
“…Clinical and animal studies provided evidence that androgens protect cavernous SM, promoting cell proliferation and maintaining functional integrity (Andersson and Wagner 1995;Aversa et al 2000Aversa et al , 2003Garban et al 1995;Huang et al 2008;Lue and Dahiya 1997;Mills et al 1992;Shabsigh 1997). It was also demonstrated that androgen deficiency contributes to endothelial damage in a castrated rat model (Lu et al 2007).…”
mentioning
confidence: 98%
“…combination with sildenafil in these patients who have dual pathology. Recent data suggest that testosterone is a smooth muscle relaxant for the penile vessels 16 which is likely to potentiate the action of sildenafil. Although no properly conducted study is available to provide hard scientific data on the efficacy of combination therapy of TRT with sildenafil, improvement in libido may increase erectile performance, thereby self-correcting borderline testosterone insufficiency.…”
Section: Discussionmentioning
confidence: 99%